Title: prospects of eco-friendliness in promoting Dhaka’s small e-businesses during COVID-19 pandemic - Pantho, Abul Hossain Chowdhury (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.